Organização política de camponeses em São Félix do Xingu - PA: estratégias, identidades e associações - KAHWAGE, Claudia Maria Carneiro (Universidade Federal do Pará, 2021)
In this work we address the issue of political organization of farmers in the municipality of São Felix do Xingu located in the southern state of Pará. Initially we emphasize in the description of the social scene and booming economic frontier in which the peasants are immersed and also try to describe historical processes of formation of the political movement of the peasants in the city that gave rise to important achievements of the category as the granting of easy credit to small farmers in the Amazon. This achievement reflected directly in coordinating the political organization of these peasants, because there was significant growth in the number of farmers' Associations in the municipality. This fact has enabled innovation in the political strategies within the movement of peasants also related to reflection and action on the part of the leaders on the situation of peasant identities representativeness and effectiveness of the category towards achievements of interests